Open mouth operations: Monetary policy by threats and arguments : the monthly meetings between the Riksbank and the commercial banks, 1956-73 - Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2023)
After World War II and prior to the financial deregulation of the 1980s, monetary policy in Sweden as well as in other western European countries rested chiefly on a system of far-reaching non-market-oriented controls of credit flows and interest rates. How was monetary policy conducted in such an environment of financial repression, where the central bank was unable to rely on traditional monetary policy instruments working on 'free' and 'unregulated' money and capital markets? This study provides an answer from the Swedish experience. It is based on a unique set of confidential minutes from about 160 monthly meetings between the Riksbank and the commercial banks during the years 1956-73. These minutes, written during or directly after the meetings, have not been available to scholars before. Most likely, a similar archive material does not exist for any other country. The examination of the minutes demonstrates that monetary policy was framed in a process involving threats and arguments in a small and closed club involving the central bank and the chief executives of the commercial banks. According to a joke assigned to Erik Lundberg 'open market operations were replaced by open mouth operations' - albeit the dialogue was kept within the club. When Swedish financial markets were deregulated in the 1980s, the standard tools of monetary policy rapidly replaced the meetings between the central bank and the commercial banks. Today, the Riksbank communicates in an open way to all financial market participants, instead of turning to a small set of commercial bankers in meetings closed to outsiders.
Keywords: B22; E42; E50; E58; E65; G21; N14; 330; Credit controls; interes rate controls; exchange controls; financial repression; liquidity ratios; the Riksbank; Sweden